Effectiveness of Friction Damper and Outrigger System on 3d RC Frame for Seismic Loading - Naveena K N; Vanishree P S, (International Journal of Emerging Science and Engineering (IJESE), 2024)
The effectiveness of the friction damper and outrigger system on a 3D RC frame for seismic loading is studied. Friction dampers have the unique property of absorbing and dissipating energy through a simple mechanism. The mechanism involved in response control involves transforming the seismic energy into heat energy through frictional forces, thus avoiding structural collapse. In the seismic active zone, the structural performance of the 3D RC frame is poor, which shows an increasing time period and excessive drifts when subjected to lateral forces. These issues can be minimized by providing lateral load-resisting elements, such as an outrigger system, at different heights of the building. Based on this G+12-storeyed 3D RC frame model, the different locations of the friction damper and outrigger system are considered in this study. Following which, the FE analysis involving the modal, equivalent static, and response spectrum analyses is performed, and results are obtained in terms of time period, base shear, storey displacement, storey drift, and acceleration, which are all tabulated and discussed.